Exploring Good Governance's Role in Sustainable Development: A Developed and Developing Countries Comparison - Kaleem, Mahmoud (International Journal of Membrane Science and Technology, 2024)
Abstracts: Good governance has emerged as a pivotal factor influencing the attainment of sustainable development goals. Its impact resonates differently across diverse socio-economic contexts, prompting the need for a comparative analysis between developed and developing countries. This research aims to evaluate the priority status and significance of the good governance agenda in driving sustainable development. By examining the practices and challenges faced by both developed and developing nations, a comprehensive understanding of the dynamics between effective governance and sustainable development is sought. This qualitative study examines the connection between good governance and sustainable development through analyzing secondary data sources. By selecting relevant and credible materials, thematic analysis identifies patterns in the relationship. Systematic processes enhance validity and reliability, although limitations stem from potential biases and lack of primary data interaction. The findings underscore the symbiotic nature of good governance and sustainable development, transcending developmental boundaries. Developed countries exhibit well-established governance practices, placing transparency, accountability, and inclusivity at the forefront. In contrast, developing nations grapple with challenges such as corruption, weak institutions, and limited resources, impacting their journey towards sustainable development. This study illuminates the paramount importance of good governance in advancing sustainable development goals, regardless of a country's developmental stage. While challenges persist, international collaboration and knowledge sharing emerge as avenues to bridge the gap between developed and developing countries. Ultimately, embracing transparent, accountable, and inclusive governance practices becomes the cornerstone of a future marked by equitable growth, environmental stewardship, and societal well-being.